SOFT REGULATION IN PRACTICE – UZBEKISTAN’S EXPERIENCE AND COMPARATIVE PERSPECTIVES ON INFORMATION RESILIENCE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines Uzbekistan’s transition from hard informational control toward softer, cooperative regulatory strategies aimed at enhancing public stability. It analyzes key reforms since 2016, including the development of a National Information Security Concept, the drafting of a new Information Code, and partnerships with international organizations in promoting media literacy and countering online extremism. Through a comparative and political-cultural lens, the study argues that soft regulation—when implemented alongside legal and institutional reforms—can strengthen information resilience and foster greater trust in institutions. Particular attention is given to the role of a relatively freer media environment in enabling constructive expression of public dissent, thereby preventing instability during periods of major socio-economic transformation.